Apparent diffusion coefficient histogram analysis for differentiating solid ovarian tumors - Liu, Renwei; Li, Ruifeng; Fang, Jinzhi; Deng, Kan; Chen, Cuimei; Li, Jianhua; Wu, Zhiqing; Zeng, Xiaoxu (Frontiers in Oncology, 2022)
Objective: To evaluate the utility of apparent diffusion coefficient (ADC) histogram analysis to differentiate between three types of solid ovarian tumors: granulosa cell tumors (GCTs) of the ovary, ovarian fibromas, and high-grade serous ovarian carcinomas (HGSOCs). Methods: The medical records of 11 patients with GCTs of the ovary (regions of interest [ROI-cs], 137), 61 patients with ovarian fibromas (ROI-cs, 161), and 14 patients with HGSOCs (ROI-cs, 113) confirmed at surgery and histology who underwent diffusion-weighted imaging were retrospectively reviewed. Histogram parameters of ADC maps (ADCmean, ADCmax, ADCmin) were estimated and compared using the Kruskal-WallisH test and Mann-Whitney U test. The area under the curve of receiver operating characteristic curves was used to assess the diagnostic performance of ADC parameters for solid ovarian tumors. Results: There were significant differences in ADCmean, ADCmax and ADCmin values between GCTs of the ovary, ovarian fibromas, and HGSOCs. The cutoff ADCmean value for differentiating a GCT of the ovary from an ovarian fibroma was 0.95×10-3 mm2/s, for differentiating a GCT of the ovary from an HGSOC was 0.69×10-3 mm2/s, and for differentiating an ovarian fibroma from an HGSOC was 1.24×10-3 mm2/s. Conclusion: ADCmean derived from ADC histogram analysis provided quantitative information that allowed accurate differentiation of GCTs of the ovary, ovarian fibromas, and HGSOCs before surgery.